Quantifying Carbon Cycle Extremes and Attributing Their Causes Under Climate and Land Use and Land Cover Change From 1850 to 2300. Issue 6 (16th June 2022) - Sharma, Bharat; Kumar, Jitendra; Collier, Nathan; Ganguly, Auroop R.; Hoffman, Forrest M.
Abstract: The increasing atmospheric carbon dioxide (CO2 ) mole fraction affects global climate through radiative (trapping longwave radiation) and physiological effects (reduction of plant transpiration). We use the simulations of the Community Earth System Model (CESM1‐BGC) forced with Representative Concentration Pathway 8.5 to investigate climate‐vegetation feedbacks from 1850 to the year 2300. Human‐induced land use and land cover change (LULCC), through biogeochemical and biogeophysical processes, alter the climate and modify photosynthetic activity. The changing characteristics of extreme anomalies in photosynthesis, referred to as carbon cycle extremes, increase the uncertainty of terrestrial ecosystems to act as a net carbon sink. However, the role of LULCC in altering carbon cycle extremes under business‐as‐usual (continuously rising) CO2 emissions is unknown. Here we show that LULCC magnifies the intensity, frequency, and extent of carbon cycle extremes, resulting in a net reduction in expected photosynthetic activity in the future. We found that large temporally contiguous negative carbon cycle extremes are due to a persistent decrease in soil moisture, which is triggered by declines in precipitation. With LULCC and global warming, vegetation exhibits increased vulnerability to hot and dry environmental conditions, increasing the frequency of fire events and resulting in considerable losses in photosynthetic activity. While most regions show strengthening of negative carbon cycle extremes, a few locations show a weakening effect driven by declining vegetation cover or benign climate conditions for photosynthesis. Increasing hot, dry, and fire‐driven carbon cycle extremes are essential for improving carbon cycle modeling and estimation of ecosystem responses to LULCC and rising CO2 mole fractions. Moreover, large aberrations in vegetation productivity represent potential and growing threats to human lives, wildlife, and food security. Plain Language Summary: Rising carbon dioxide (CO2 ) emissions due to human activities, such as fossil fuel burning and land use and land cover change (LULCC), are the major driver of climate change. Heatwaves, droughts, and fires have increased and are expected to accelerate with climate change in the twenty‐first century and beyond. This increase in extreme climate conditions has the potential to further alter vegetation productivity (called gross primary production or GPP) and carbon uptake capacity. Here, we use a global Earth system model to investigate the impacts of (a) CO2 forcing and (b) CO2 and LULCC forcing on the intensity, frequency, and duration of extreme events in GPP. We found that the negative extremes in GPP, which are associated with higher losses in carbon uptake than expected, increase at a higher rate than positive GPP extremes; and this rate rises with LULCC forcing. The most dominant climate driver causing the GPP extremes is soil moisture anomalies, which are triggered by extremes in precipitation and temperature. The lagged responses of climate drivers on GPP extremes vary with the drivers and spatial location. The largest number of GPP extremes were driven by the compound effect of water‐, temperature‐, and fire‐related drivers. Key Points: Human activities, through land‐use change, lead to increased intensity, duration, and frequency of negative extremes in gross primary productivity (GPP) Soil moisture anomalies are the dominant driver of GPP extremes, followed by fire and daily maximum temperature The regions with overall reduction in GPP often show weakening of negative extremes in GPP